Pentingnya Kewaspadaan Berinternet untuk Kesehatan Mental Anak dan Remaja - Yuliana Yuliana (Penerbit Goodwood, 2022)
Purpose: To describe the ways in increasing the internet awareness for the mental health of the children and adolescent. Methodology/approach: It is a narrative literature review. Articles were taken from the Science Direct and Google Scholar databases. Inclusion criteria are review and research articles. The excluded articles that were not peer-reviewed and unavailable full-text paper. Articles were read twice to reduce the bias. The selected articles were summarized and narrated descriptively. Results/findings: Results revealed that cybersecurity awareness can be increased by digital literacy training. Children should be taught how to avoid risky online behaviour to increase the mental health of the children. The cybersecurity awareness program is good to be given to children in avoiding phishing, pornography, cyberbullying, identity theft, and breaking to privacy. Children must be taught how to keep their passwords safe and private. They also need to be more cautious when playing online games. Limitations: It is a narrative literature review, the result is not as accurate as a study. Contribution: The contribution is the digital literation and cyber security program can be taught to the children to keep the good mental health during the COVID-19 pandemic and the time beyond.